ANALISIS TERHADAP STRUKTUR KURIKULUM TINGKAT ALIYAH DAN DAMPAKNYA TERHADAP PEMBELAJARAN DI MADRASAH TARBIYAH ISLAMIYAH CANDUNG KAB. AGAM - Nelly Izmi (El-Rusyd, 2018)
Issues raised in this research is that how the structure of the curriculum inMTI Candung, infact, there are six subjects were naming the same curriculum ofKitab Kuning and the curriculum of the Religion Minister of Indonesia, the content ofthe curriculum is also partly the same, but are taught at different times, so there hasbeen a dualism curriculum that makes its implementation to be less effective andefficient, and what the inpact of a dualism curriculum to the teaching and learningprocess. The method used in this study is qualitative. While data collection is donethrough interview, observation and documentation. This data analysis techniquebased on verification, interpretation, and historiography. Based on the collecteddata, obtained the following results:The weakness found were: learning outcome isless than optimal, manages more personnel because the same field of study are taughttwice, to pay salary / incentive larger, there is more reguler schedules and studentsfeel the burden of learning and a severe test, because it was done twice